The interval-based physiological and mechanical demands of cross-country ski training - Haugnes, P.; Kocbach, J.; Luchsinger, H.; Ettema, G.; Sandbakk, O. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate fluctuations in speed, work rate, and heart rate (HR) when cross-country ski skating across varying terrains at different endurance-training intensities. Methods: Seven male junior Norwegian skiers performed maximal-speed (Vmax) tests in both flat and uphill terrains. Thereafter, 5-km sessions at low (LIT), moderate (MIT), and high intensity (HIT) were performed based on their own perception of intensity while monitored by a global navigation satellite system with integrated barometry and accompanying HR monitor. Results: Speed, HR, and rating of perceived exertion gradually increased from LIT to MIT and HIT, both for the total course and in flat and uphill terrains (all P<.05). Uphill work rates (214 [24] W, 298 [27] W, and 350 [54] W for LIT, MIT, and HIT, respectively) and the corresponding percentage of maximal HR (79.2% [6.1]%, 88.3% [2.4]%, and 91.0% [1.7]%) were higher than in flat terrain (159 [16] W, 206 [19] W, and 233 [72] W vs 72.3% [6.3]%, 83.2% [2.3]%, and 87.4% [2.0]% for LIT, MIT, and HIT, respectively) (all P<.01). In general, ~13% point lower utilization of maximal work rate was reached in uphill than in flat terrain at all intensities (all P<.01). Conclusions: Cross-country ski training across varying terrains is clearly interval based in terms of speed, external work rate, and metabolic intensity for all endurance-training intensities. Although work rate and HR were highest in uphill terrain at all intensities, the utilization of maximal work rate was higher in flat terrain. This demonstrates the large potential for generating external work rate when uphill skiing and the corresponding downregulation of effort due to the metabolic limitations.